Seasonal influenza vaccination of healthcare workers: systematic review of qualitative evidence - Theo Lorenc; David Marshall; Kath Wright; Katy Sutcliffe; Amanda Sowden (BMC, 2017)
Abstract Background Most countries recommend that healthcare workers (HCWs) are vaccinated seasonally against influenza in order to protect themselves and patients. However, in many cases coverage remains low. A range of strategies have been implemented to increase uptake. Qualitative evidence can help in understanding the context of interventions, including why interventions may fail to achieve the desired effect. This study aimed to synthesise evidence on HCWs' perceptions and experiences of vaccination for seasonal influenza. Methods Systematic review of qualitative evidence. We searched MEDLINE, EMBASE and CINAHL and included English-language studies which reported substantive qualitative data on the vaccination of HCWs for seasonal influenza. Findings were synthesised thematically. Results Twenty-five studies were included in the review. HCWs may be motivated to accept vaccination to protect themselves and their patients against infection. However, a range of beliefs may act as barriers to vaccine uptake, including concerns about side-effects, scepticism about vaccine effectiveness, and the belief that influenza is not a serious illness. HCWs value their autonomy and professional responsibility in making decisions about vaccination. The implementation of interventions to promote vaccination uptake may face barriers both from HCWs' personal beliefs and from the relationships between management and employees within the targeted organisations. Conclusions HCWs' vaccination behaviour needs to be understood in the context of HCWs' relationships with each other, with management and with patients. Interventions to promote vaccination should take into account both the individual beliefs of targeted HCWs and the organisational context within which they are implemented.